2016
DOI: 10.1159/000443052
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Effect of Androgen Receptor Inhibition in Mesenchymal Stem-Like Triple-Negative Breast Cancer

Abstract: Background/Aims: Androgen receptor (AR), a steroid hormone receptor, has recently emerged as prognostic and treatment-predictive marker in breast cancer. Previous studies have shown that AR is widely expressed in up to one-third of triple-negative breast cancer (TNBC). However, the role of AR in TNBC is still not fully understood, especially in mesenchymal stem-like (MSL) TNBC cells. Methods: MSL TNBC MDA-MB-231 and Hs578T breast cancer cells were exposed to various concentration of agonist 5-α-dihydrotestoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 36 publications
3
48
0
1
Order By: Relevance
“…In line with our published data, which demonstrated that AR inhibitor exhibits antiproliferative effect in mesenchymal stem-like (MSL) TNBC cells [22], we observed the positive effect of DHT, a well-known AR agonist, on cellular viability of two AR-positive MSL TNBC cells, namely MDA-MB-231 and Hs578T. We assessed the positive action of increasing concentrations of DHT at 0.1 to 100 n M on MDA-MB-231 and Hs578T cells by MTT assay.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In line with our published data, which demonstrated that AR inhibitor exhibits antiproliferative effect in mesenchymal stem-like (MSL) TNBC cells [22], we observed the positive effect of DHT, a well-known AR agonist, on cellular viability of two AR-positive MSL TNBC cells, namely MDA-MB-231 and Hs578T. We assessed the positive action of increasing concentrations of DHT at 0.1 to 100 n M on MDA-MB-231 and Hs578T cells by MTT assay.…”
Section: Resultssupporting
confidence: 91%
“…Our previous studies have revealed that DHT treatment significantly accelerated the in vivo growth of MDA-MB-231 xenograft tumors in comparison with the control treatment [22]. In the present study, to assess the effects of DHT treatment on AR and GPER levels in the primary tumor xenografts, IHC staining analysis was conducted on the harvested xenogrft tumors obtained from our previous experiment as mentioned.…”
Section: Resultsmentioning
confidence: 99%
“…Such roles have been extensively studied in adaptive immunity and secondary lymphoid organogenesis [13, 14]. The CCR7 -null mice mutant displayed a disrupted architecture of the thymus and lymph nodes, as well as reduced primary immune response [9].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the molecular mechanisms that regulate the EMT process is crucial for improving breast carcinoma treatment [22, 23]. Our study showed that ectopic expression of miR-212-5p in TNBC cells impaired their invasion, proliferation and growth.…”
Section: Discussionmentioning
confidence: 83%